The influence of glycerol hyperhydration on run performance in an Olympic distance triathlon - van Ewyk, G. T. (2005)
This study was designed to determine the benefits of glycerol hyperhydration over a placebo hyperhydration as a pre-race strategy and its influence on the run performance during an Olympic distance triathlon. Ten competitive triathletes (mean VO2 peak = 64.3 ml.min -1 .kg -1) undertook two simulated Olympic distance triathlons in 31 C and 61 % relative humidity. The trials were split into two work phases: a fixed workload phase comprising of a 18-20 min swim and a 60 min cycle and, a self regulated time trial run over 10 kilometres on a treadmill. 2.5 hours before each trial either a glycerol solution (1 g/kg body mass in a 4% carbohydrate - electrolyte drink) or a placebo of equal volume of the 4% carbo-electrolyte solution was ingested. The total fluid intake in each trial was 23 ml/kg body mass (BM). A double blind, cross over design with respect to glycerol was used in respect to the treatments. Glycerol ingestion expanded body water over the placebo by 150 ml (26%). At 30,60 and 90 minutes after the start of drinking, urine output was significantly higher with the glycerol treatment than placebo (58.4, 239.8 and 399.8 ml vs 40, 101.3 and 276.9 ml). Peak mean urine volume for glycerol occurred at 90 minutes (399.8 ml) while placebo peaked at 120 minutes (417.7 ml). Glycerol treatment had improved the performance of five of the subjects in respect to finishing time (7.0, 2.4 and 2.7%) and total distance covered (40 and 12%) in the self regulated time trial run. However, while 4 of the 5 subjects didn't complete the run with the glycerol treatment, only 2 subjects failed to finish with the placebo treatment. There were no significant differences in rectal temperature, plasma volume expansion, mean skin temperature and heart rates between trials. However, glycerol did produce significantly higher blood lactates (p<0.05) during the run than the placebo. In the glycerol treatment, four out of ten subjects did not complete the 10 km while five athletes complained of bloating and nausea in the glycerol trial. Data from this study suggests that glycerol induced performance did not result from plasma volume expansion and subsequent lower core temperature and lower heart rates.